Pengaruh Penerapan Metode Mengajar Resiprokal Terhadap Gerak Dasar Lay Up Shoot dalam Permainan Bola Basket pada Siswa Putra SMA N 1 Tomohon - Marsellino Willem Rindengan; Mesak A.S.F. Rambitan; Djoni Sunkudon (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Reciprocal method in this style students work together with their friends and give feedback to their friends, based on criteria determined by the teacher. Basketball is a sport that is competed throughout the world, basketball is one of the big ball games taught at the high school level. Basketball is a sport that uses a large ball and is used by hand and played in groups, each group consisting of two teams of 5 people each. This study aims to examine the application of reciprocal teaching style in improving the mastery of Lay Up Shoot basic movements in basketball games in male students of SMA Negeri 1 Tomohon. The instrument used in this study was a test of mastery of the basic movements of Lay Up Shoot in basketball games. The results of this study indicate that the average increase in mastery of Lay Up Shoot basic movements in basketball games in the experimental group using a reciprocal teaching style is better than the average increase in mastery of Lay Up Shoot basic movements in basketball games in the control group who did not get treatment.